Fast and Efficient Removal of Uranium onto a Magnetic Hydroxyapatite Composite: Mechanism and Process Evaluation - Tao Ou (MDPI AG, 2021)
The exploration and rational design of easily separable and highly efficient sorbents with satisfactory capability of extracting radioactive uranium (U)-containing compound(s) are of paramount significance. In this study, a novel magnetic hydroxyapatite (HAP) composite (HAP@ CoFe2O4), which was coupled with cobalt ferrite (CoFe2O4), was rationally designed for uranium(VI) removal through a facile hydrothermal process. The U(VI) ions were rapidly removed using HAP@ CoFe2O4 within a short time (i.e., 10 min), and a maximum U(VI) removal efficiency of 93.7% was achieved. The maximum adsorption capacity (Qmax) of the HAP@CoFe2O4 was 338 mg/g, which demonstrated the potential of as-prepared HAP@CoFe2O4 in the purification of U(VI) ions from nuclear effluents. Autunite [Ca(UO2)2(PO4)2(H2O)6] was the main crystalline phase to retain uranium, wherein U(VI) was effectively extracted and immobilized in terms of a relatively stable mineral. Furthermore, the reacted HAP@CoFe2O4 can be magnetically recycled. The results of this study reveal that the suggested process using HAP@CoFe2O4 is a promising approach for the removal and immobilization of U(VI) released from nuclear effluents.